Increased CXCL4 expression in hematopoietic cells links inflammation and progression of bone marrow fibrosis in MPN - Gleitz, Hélène; Dugourd, Aurélien; Sáez Rodríguez, Julio (Blood, 2020)
In primary myelofibrosis (PMF), bone marrow fibrosis is driven by normal stromal cells in the context of hematopoietic stem cells (HSCs) that carry myeloprolife
Gesehen am 26.11.2020